PENGARUH PENILAIAN KINERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAERAH KABUPATEN SIDENRENG RAPPANG - Rusni Rusni (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
This study aims to determine the effect on the productivity performance appraisal of employees working in the office staffing agency Sidrap district and to determine the factors that affect the assessment of the performance of employee productivity in the Office of the Regional Employment Board Sidenreng Rappang. The study design used in this research is descriptive quantitative by focusing on the influence of performance appraisal. The population in this study were all employees in the Office of the Regional Employment Board Sidenreng Rappang. The methods of data collection are observation, interview, questionnaire and literature study. The collected data is then processed and analyzed by using quantitative descriptive analysis with frequency table. Based on the research we concluded that indicators of employee performance evaluation at the district office staffing bada Sidrap with 75.73% considered good value and employee productivity indicators at district office staffing agency Sidrap at 74.77% while the value factors affect the assessment of the performance of employee productivity in the Office of the Regional employment Board Sidenreng Rappang rated 66.38% considered good.